2011
DOI: 10.1542/peds.2011-0841
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Exclusive Breastfeeding in the United States

Abstract: OBJECTIVES: To estimate the proportions of US infants who were breastfed exclusively for 6 months, according to characteristics of the mother, child, and household environment, and to compare associations between those characteristics and exclusive breastfeeding with associations between those characteristics and breastfeeding initiation. METHODS: Data were obtained from the 2007 National Survey of Children's Health, a nation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
183
16
10

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(231 citation statements)
references
References 28 publications
22
183
16
10
Order By: Relevance
“…In the present study, early weaning was reported in approximately 30% of the sample, a value higher than expected according to WHO [13]. The same trend has also been observed in other studies [10,14,17,18].…”
Section: Discussionsupporting
confidence: 89%
“…In the present study, early weaning was reported in approximately 30% of the sample, a value higher than expected according to WHO [13]. The same trend has also been observed in other studies [10,14,17,18].…”
Section: Discussionsupporting
confidence: 89%
“…On the other hand, the IFPS II sample was largely Caucasian, educated, and well off. Given the direct association between low socioeconomic status and breastfeeding difficulties in our sample and in other studies, 43 our analysis BMI, body mass index; EPDS, Edinburgh Postnatal Depression Scale; MV, multivariable; OR, odds ratio.…”
Section: Discussionmentioning
confidence: 94%
“…A 2007 National Survey of Children' s Health study in .25 000 children aged 6 months through 5 years revealed that although children with birth weights ,1500 g were more likely to have been breastfed than children with normal or above-normal birth weights, this trend was not observed among children born with birth weights of 1500 to ,2500 g. 19 A possible reason for these findings is that premature infants are not fed by mouth until they reach ∼34 weeks' postconception age and mothers of very preterm and/or very low birth weight infants who are interested in breastfeeding are pumping and storing breast milk to be fed via gavage tubes. On the other hand, mothers of LPT infants and/or moderately low birth weight infants who are interested in breastfeeding are most likely attempting to breastfeed shortly after birth and may confront feeding difficulties due to their infant' s developmental immaturity, which may preclude them from continuation.…”
Section: Breastfeedingmentioning
confidence: 99%